2008
DOI: 10.1002/elps.200700585
|View full text |Cite
|
Sign up to set email alerts
|

Analytical optimization of nanocomposite surface‐enhanced Raman spectroscopy/scattering detection in microfluidic separation devices

Abstract: Adding vibrational spectroscopies to the arsenal of detection modes for microfluidics (mufluidics) offers benefits afforded by structurally descriptive identification of separated electrophoretic bands. We have previously applied surface-enhanced Raman spectroscopy (SERS) detection with nanocomposite metal-elastomer substrates as a detection mode in mufluidic channels. To create these mufluidic-SERS devices, silver-PDMS substrate regions are integrated into the architecture of a separation chip fabricated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 36 publications
1
43
0
Order By: Relevance
“…An integrated separation and SERS detection micro-fluidic device was reported by Connatser et al [31], as shown in Figure 7.7. Designed patterns for substrates were written into an e-beam-sensitive layer using e-beam lithography and then coated with 25 nm of silver or gold via vapour deposition.…”
Section: Other Separation Methodsmentioning
confidence: 99%
“…An integrated separation and SERS detection micro-fluidic device was reported by Connatser et al [31], as shown in Figure 7.7. Designed patterns for substrates were written into an e-beam-sensitive layer using e-beam lithography and then coated with 25 nm of silver or gold via vapour deposition.…”
Section: Other Separation Methodsmentioning
confidence: 99%
“…To achieve more detailed and richer information about an analyte (Baker et al, 2009), TLS could also be combined with other detection techniques, such as fluorescence detection, electrochemical analysis, MS, surface-enhanced Raman scattering (qualitatively identifying analytes; Connaster et al, 2008), and surface plasmon resonance (studying binding interactions in biological assays without use of labels; Luo et al, 2008).…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…Surface-immobilized SERS substrates have been prepared on the elastomer surface [9] by deposition of thin silver films into nanowells for the detection of rhodamine 6G and adenosine. SERS substrates formed by the deposition of silver composites and fabrication of three-dimensional nanostructures by electron beam lithography [10] have been applied for the detection of rhodamine 6G, resorufin, para-aminobenzoic acid, ortho-phenanthroline, 6-amino-2-naphthoic acid and terephthalic acid. Other approaches are the deposition of nanoparticles (see also Chapter 2) or nanostructured noble-metal films.…”
Section: Microfluidic Large-scale Integration and Pdms Microchannelsmentioning
confidence: 99%